Anti-SLAPP Policy Conceptualization as a Strategic Effort to Protect Indigenous Peoples' Environmental Rights from Judicial Harassment - Jumantoro, Tegar Raffi Putra; Novemyanto, Alfin Dwi (Journal of Progressive Law and Legal Studies, 2025)
Human Rights regulation has been implemented in several positive laws of international countries, including Indonesia. All citizens are entitled to equal rights and status through human rights, and the state, including indigenous peoples, must guarantee their fulfillment. The guarantee of protection for the rights of indigenous peoples has been regulated by law. However, its implementation has not been fully realized. This statement is evidenced by findings of field conflict records and instances of judicial harassment between indigenous communities and environmental management companies. The government subsequently introduced the Anti-SLAPP policy to allow vulnerable groups to present proposals, criticisms, and ideas in their fight for social justice and fulfilling their environmental rights. Addressing these issues, this research aims to analyze the relationship between the fulfillment of indigenous peoples' rights to the environment and instances of judicial harassment, evaluate the conceptualization of Anti-SLAPP principles within Indonesia's positive legal framework, and examine the implementation of Anti-SLAPP principles in various international countries. This normative juridical study is conducted using legislative, conceptual, and comparative approaches, and it utilizes secondary data from primary and secondary legal materials to analyze legal issues related to anti-SLAPP. Through various legal approaches and theories, the findings of this research reveal several weaknesses in Indonesia's Anti-SLAPP policy. The researcher provides recommendations, including a comprehensive study on the need for a specific Anti-SLAPP law and the necessity for law enforcement officers to prioritize persuasive and non-repressive efforts, ensuring transparency in the environmental management permitting process.